2015
DOI: 10.1186/s12885-015-1941-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of direct access to CT scan in early lung cancer detection: an unblinded, cluster-randomised trial

Abstract: BackgroundLower lung cancer survival rates in Britain and Denmark compared with surrounding countries may, in part, be due to late diagnosis. The aim of this study was to evaluate the effect of direct access to low-dose computed tomography (LDCT) from general practice in early lung cancer detection on time to diagnosis and stage at diagnosis.MethodsWe conducted a cluster-randomised, controlled trial including all incident lung cancer patients (in 19-month period) listed with general practice in the municipalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 31 publications
0
28
1
Order By: Relevance
“…Despite advances in surgical, radiotherapeutic and chemotherapeutic strategies, lung cancer is an aggressive and heterogeneous disease, and therefore the long-term survival rate remains low (5)(6)(7). Lung cancer treatment is complex for numerous reasons, including hard-to-detect early symptoms, early metastasis and vascular factors that mediate drug-resistance and disease progression (8)(9)(10). Previous studies have investigated inhibiting angiogenesis and antagonizing vascular endothelial growth factors as potential therapeutic targets for the treatment of lung cancer (11,12); however, the potential of this strategy remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Despite advances in surgical, radiotherapeutic and chemotherapeutic strategies, lung cancer is an aggressive and heterogeneous disease, and therefore the long-term survival rate remains low (5)(6)(7). Lung cancer treatment is complex for numerous reasons, including hard-to-detect early symptoms, early metastasis and vascular factors that mediate drug-resistance and disease progression (8)(9)(10). Previous studies have investigated inhibiting angiogenesis and antagonizing vascular endothelial growth factors as potential therapeutic targets for the treatment of lung cancer (11,12); however, the potential of this strategy remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, I outlined an anthropology of sensations as a framework for understanding symptoms as cultural configurations and briefly illustrated its utility for exploring more overall relations between biomedical knowledge production and everyday, embodied experience and the building of contemporary forms of disease sensitisation. of those given the option of a CT scan) is encouraged to do follow-up scans for up to two years after their initial diagnostic investigation (Guldbrandt et al, 2015). 7 Conversations on human sense-modals date back to Aristotle and his presentation of the five-sense-modal.…”
Section: Resultsmentioning
confidence: 99%
“…Computerised tomography (CT) scanners and access to digital imaging technologies have, for example, altered diagnostic potential for lung cancers in Denmark (Guldbrandt et al, 2015), and the introduction of capsule endoscopy is expected to lead to ear- …”
Section: The Introduction Of Magnetic Resonance Imaging (Mri) Scannermentioning
confidence: 99%
“…There is an emerging literature regarding allowing GPs access to low-dose CT, for patients with symptoms where lung cancer is suspected ( Guldbrandt et al , 2014 ). However, a recent cluster trial in Denmark reported little improvement in stage or times to diagnosis with direct access to CT ( Gulbrandt et al , 2015 ). This trial had different inclusion criteria to our design, hence it is unknown what effect on outcomes an individually randomised trial of direct access to CT for ‘extra-NICE' symptoms would be.…”
Section: Figurementioning
confidence: 99%